Isolated fetal ascites as a presentation of intestinal atresia - Filipa Miranda; Joana Soares; Catarina Carvalho; Hélder Morgado; Carmen Carvalho; Elisa Proença (Journal of Pediatric and Neonatal Individualized Medicine, 2022)
Isolated fetal ascites is a rare condition and its natural history needs further research. We describe a case of progressive fetal isolated ascites diagnosed at 22 weeks of gestation associated with hyperechogenic bowel in a primiparous woman. Genetic abnormalities, infection and metabolic causes were excluded. An elective C-section was performed at 29 weeks of gestation after no clinical improvement was obtained with paracentesis. After birth, X-ray and ultrasonography showed high-volume ascites and enlarged liver. On the 5th day of life, no meconium had passed and an abdominal X-ray was repeated: pneumoperitoneum was diagnosed.